Kejahatan Transnasional Terorganisir di Wilayah Perbatasan: Studi Modus Operandi Penyelundupan Narkotika Riau dan Malaysia - Rendi Prayuda (Andalas Journal of International Studies (AJIS), 2020)
The transformation of issues in international politics has led to a shift from traditional security issues (war and military) to non-traditional security issues (human security). One form of non-traditional security threat is the transnational crime activity of narcotics smuggling in Southeast Asia. The Southeast Asian region has an area of around 4.4 million KM2 and is known as the "Golden Triangle" narcotics production area on the border of Thailand, Laos, and Myanmar. One of the destination countries for smuggling narcotics in the Southeast Asian region is Indonesia and Riau Province is one of the gateways for the illegal entry of narcotics from other countries, especially Malaysia. This paper aims to analyze the modus operandi of transnational crime in narcotics smuggling in the border regions of Riau and Malaysia. This paper uses a qualitative method using interviews with research informants. The results of this study indicate that the modus operandi of narcotics smuggling in the border regions of Indonesia and Malaysia is carried out by sea along the coastline of the border provinces of Riau and Malaysia. Narcotics are neatly wrapped and installed GPS devices then smuggled at night by using the services of fishermen as a courier. This seawater smuggling route was chosen due to several factors, namely: the proximity of the territorial waters, the number of unofficial or illegal ports, the lack of surveillance patrols along the water area and the professionalism of law enforcement officers in the border region. The transformation of issues in international politics has led to a shift from traditional security issues (war and military) to non-traditional security issues (human security). One form of non-traditional security threat is the transnational crime activity of narcotics smuggling in Southeast Asia. The Southeast Asian region has an area of around 4.4 million KM2 and is known as the "Golden Triangle" narcotics production area on the border of Thailand, Laos, and Myanmar. One of the destination countries for smuggling narcotics in the Southeast Asian region is Indonesia and Riau Province is one of the gateways for the illegal entry of narcotics from other countries, especially Malaysia. This paper aims to analyze the modus operandi of transnational crime in narcotics smuggling in the border regions of Riau and Malaysia. This paper uses a qualitative method using interviews with research informants. The results of this study indicate that the modus operandi of narcotics smuggling in the border regions of Indonesia and Malaysia is carried out by sea along the coastline of the border provinces of Riau and Malaysia. Narcotics are neatly wrapped and installed GPS devices then smuggled at night by using the services of fishermen as a courier. This seawater smuggling route was chosen due to several factors, namely: the proximity of the territorial waters, the number of unofficial or illegal ports, the lack of surveillance patrols along the water area and the professionalism of law enforcement officers in the border region.